2017
DOI: 10.15252/msb.20167386
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling links Wnt signaling to emergent patterns of metabolism in colon cancer

Abstract: Cell‐intrinsic metabolic reprogramming is a hallmark of cancer that provides anabolic support to cell proliferation. How reprogramming influences tumor heterogeneity or drug sensitivities is not well understood. Here, we report a self‐organizing spatial pattern of glycolysis in xenograft colon tumors where pyruvate dehydrogenase kinase (PDK1), a negative regulator of oxidative phosphorylation, is highly active in clusters of cells arranged in a spotted array. To understand this pattern, we developed a reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 67 publications
3
44
1
Order By: Relevance
“…Turing models of metabolism in colon cancer link Wnt signalling and gene circuits. We propose that these gene circuits represent potentially promising novel colon cancer targets to model mathematically . A preclinical confocal colonoscopy study demonstrated that a CLDN1‐binding peptide can visualize overexpressed CLDN1 in colonic adenomas in vivo , and actomyosin meshwork measurements have been used to demonstrate morphogenesis.…”
Section: Some Potential Applications Of Turing Pattern Analysis In Gamentioning
confidence: 99%
See 2 more Smart Citations
“…Turing models of metabolism in colon cancer link Wnt signalling and gene circuits. We propose that these gene circuits represent potentially promising novel colon cancer targets to model mathematically . A preclinical confocal colonoscopy study demonstrated that a CLDN1‐binding peptide can visualize overexpressed CLDN1 in colonic adenomas in vivo , and actomyosin meshwork measurements have been used to demonstrate morphogenesis.…”
Section: Some Potential Applications Of Turing Pattern Analysis In Gamentioning
confidence: 99%
“…We propose that these distinctive colon mucosa patterns support the presence of morphogenetic feedback mechanisms which are hypothesized to regulate the topological architecture of tissues . Integrating our knowledge about gene circuits and tissue topology mathematically may help to guide the development of novel interventions targeting the glucocorticoid/Notch/Wnt pathways . Dynamic 4D Nucleome algorithms may provide a more powerful predictive model of colon cancer with the applications of machine learning methods …”
Section: Some Potential Applications Of Turing Pattern Analysis In Gamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that Wnt signalling can also play a direct role in regulating cancer cell metabolism (Lee et al, , ; Pate et al, ; Sherwood et al, ; Sprowl‐Tanio et al, ). For example, Wnt signalling controls cancer cell metabolism via the regulation of pyruvate dehydrogenase kinase 1 and (Pate et al, ; Sprowl‐Tanio et al, ).…”
Section: Targeting Downstream Gene Programmes Regulated By Tcf/lef–β‐mentioning
confidence: 99%
“…Regulation of both these genes results in cancer cells favouring aerobic glycolysis or Warburg metabolism, which potentiates a unique therapeutic target in Wnt‐high cancers. Additionally, mathematical modelling and in vitro assays show that a combination therapy targeting Wnt signalling and glycolytic activity has a synergistic effect (Lee et al, ). Currently, there are at least a dozen cancer metabolism drugs in clinical trials, some of which are promising – such as those targeting isocitrate dehydrogenase (IDH1) (Agios®), glutaminase inhibitor CB‐839 from Calithera®, and fatty acid synthase inhibitor TVB‐2640 from 3‐V Biosciences® (Garber, ; Mullard, ).…”
Section: Targeting Downstream Gene Programmes Regulated By Tcf/lef–β‐mentioning
confidence: 99%